Synthesis And Performance Of Ordered Mesoporous Sno2 Using Kit-6 Nanocasting For Detection Of Hydrogen Sulphide Gas - Sattigamurti, Thibbaganesh (Universiti Sains Malaysia, 2022)
In the realm of harmful gas detection, tin oxide(SnO2) based sensors have garnered a lot of interest because of their sensitive, quick response and stable over the long run. However, the sensitivity and performance of SnO2 based sensor still require further research. This work focuses on the synthesis and performance of nanocasted ordered mesoporous SnO2 using KIT-6 mesoporous silica for detection of hydrogen sulphide gas. Synthesis of the KIT-6 was done using pluronic P-123 triblock copolymer, HCL and tetraethoxysilane, followed by hydrothermal treatment using oil bath at temperature 80°C and 100°C. Hydrothermal aging temperature 80°C exhibits better pore structure and surface area then 100°C . The produced ordered mesoporous SnO2 was compared using two different types of infiltration which are the solid-liquid method and conventional evaporation method. Based on the structural properties obtain from XRD, BET and SEM characterization, it shows that conventional evaporation method exhibits better structure. Subsequently, the detection hydrogen sulphide gas was carried out using MATLAB based on the obtained physical properties of the developed ordered mesoporous SnO2. The influence of hydrogen sulphide concentration quantity and operating temperature on the sensitivity of a gas sensor was explored with the help of a diffusion mechanism model in order to discover the most effective methods for optimising the gas sensing trends of mesoporous SnO2. The result obtained for the gas concentration on the sensitivity shows a well resolved curve as concentration increases the sensitivity increases until a saturation point which suits the experimental result from the research paper. By comparing the operating temperature against the sensitivity with varying concentration of the sensor it exhibits a bell-shaped curve which correlates with experimental data from the research papers. Finally, sensitivity analysis was performed based on the film thickness (L), as well as pore size (r).Both of the analysis showed that simulated curve with experiment data conducted based on this research correlates with experimental data of gas sensing results from the research papers which are explained detailed in this study. Based on the 17 Sustainable Development Goals, goal 13 suits the studies. Goal 13 was about climate changes, where it’s about increasing countries' ability to withstand and recover from natural disasters and climate related hazards. To have early precaution caused by the hazardous hydrogen sulphide gas to environment, this sensor will be a perfect way to monitor the hydrogen sulphide pollution amount.